Hubungan Tingkat Stres dengan Perilaku Merokok pada Remaja di Cisaranten Kulon II RT 07 RW 05 Kelurahan Cisaranten Kulon - Soares, Native Marques; Hariningsih, Wintari; Prasetyo, Yunus Adhy (Institut Kesehatan Immanuel, 2025)
Smoking behavior is a consistent action among adolescents, leading to an increasing number of smokers and a decrease in the age of smokers. This is attributed to the belief that cigarettes serve as calming agents during moments of anxiety and stress. This study aims to identify the stress levels among male adolescents in Cisaranten Kulon II RT 07 RW 05, Bandung, and to analyze the relationship between stress levels and smoking behavior in the same group. The research employs a quantitative approach to explore the connections between independent and dependent variables. The study population comprises all adolescents aged 10-19 residing in Cisaranten Kulon II RT 07 RW 05, Bandung, in 2023, totaling 85 male adolescents. Due to the small population size, the research will employ a total sampling method, where all individuals become part of the sample. Data will be collected through questionnaires distributed to all participants, including an explanation of the research's objectives.The data will be analyzed using the Spearman Rank correlation technique. Based on the research outcomes, the respondents' profile indicates that 65.8% fall within the age range of 10-15 years, 40.0% have elementary-level education, 48.2% exhibit positive smoking behavior, and 34.1% experience mild stress levels. The research reveals a significant relationship between stress levels and smoking behavior with a P-Value of 0.001, indicating a connection between the two variables. Therefore, the study establishes that there is a relationship between stress levels and smoking behavior among male adolescents in Cisaranten Kulon II RT 07 RW 05.